Condition of the Muslim Community Around Banyuputih After the Closure of Localizations - Akhmad Nurasikin; Achmad Munib; Ali Imron; Ali Romdhoni (Islamic Review, 2023)
The Banyuputih localization complex started with the construction of the Banyuputih truck base around 1976 and then developing into a karaoke and prostitution place. This study aims to look at the socioeconomic circumstances of the Muslim neighborhood around the Banyuputih brothel after it was shut down by the Batang District Government in 2021. The type of research used is field research and uses a phenomenologi approach. Methods of data collection using observation, interviews and documentation. As for data analysis using descriptive qualitative analysis. The study's findings demonstrate that a thorough process of closing the localization complex and converting it to an Islamic center was followed, along with numerous considerations, rigorous research, and extensive outreach. Parents' growing conviction that young people are becoming more moral and that the use of alcohol and illegal drugs is declining has a positive social impact on the neighborhood. It is also a place for child-friendly religious tourism. The economic impact that is felt is a decrease in the amount of income until various adaptations are made such as switching professions, switching customers and controlling family needs.